Detection of OH in an atmospheric flame at 1.5 um using optical frequency comb spectroscopy - Rutkowski, Lucile; Johansson, Alexandra C.; Valiev, Damir; Khodabakhsh, Amir; Tkacz, Arkadiusz; Schmidt, Florian M.; Foltynowicz, Aleksandra (Photonics Letters of Poland, 2016)
We report broadband detection of OH in a premixed CH4/air flat flame at atmospheric pressure using cavity-enhanced absorption spectroscopy based on an Er:fiber femtosecond laserand a Fourier transform spectrometer.By taking ratios of spectra measured at different heights above the burner we separate twenty OH transitions from the largely overlapping water background. Weretrieve from fits to the OH lines the relative variation of the OH concentration and flame temperature with height above the burner and compare them with 1-D simulations of the flamestructure. Full Text: PDF References G. Meijer, M. G. Boogaarts, R. T. Jongma, D. H. Parker and A. M. Wodtke, "Coherent cavity ring down spectroscopy", Chem. Phys. Lett. 217, 1, 112 (1994). CrossRef S. Cheskis, I. Derzy, V. A. Lozovsky, A. Kachanov and D. Romanini, "Cavity ring-down spectroscopy of OH radicals in low pressure flame", Appl. Phys. B 66, 3, 377 (1998). CrossRef X. Mercier, E. Therssen, J. F. Pauwels and P. Desgroux, "Cavity ring-down measurements of OH radical in atmospheric premixed and diffusion flames.: A comparison with laser-induced fluorescence and direct laser absorption", Chem. Phys. Lett. 299, 1, 75 (1999). CrossRef J. Scherer, D. Voelkel and D. Rakestraw, "Infrared cavity ringdown laser absorption spectroscopy (IR-CRLAS) in low pressure flames", Appl. Phys. B 64, 6, 699 (1997). CrossRef R. Peeters, G. Berden and G. Meijer, "Near-infrared cavity enhanced absorption spectroscopy of hot water and OH in an oven and in flames", Appl. Phys. B 73, 1, 65 (2001). CrossRef T. Aizawa, "Diode-laser wavelength-modulation absorption spectroscopy for quantitative in situ measurements of temperature and OH radical concentration in combustion gases", Appl. Opt. 40, 27, 4894 (2001). CrossRef B. Löhden, S. Kuznetsova, K. Sengstock, V. M. Baev, et al., "Fiber laser intracavity absorption spectroscopy for in situ multicomponent gas analysis in the atmosphere and combustion environments", Appl. Phys. B 102, 2, 331 (2011). CrossRef A. Matynia, M. Idir, J. Molet, C. Roche, et al., "Absolute OH concentration profiles measurements in high pressure counterflow flames by coupling LIF, PLIF, and absorption techniques", Appl. Phys. B 108, 2, 393 (2012). CrossRef R. S. Watt, T. Laurila, C. F. Kaminski and J. Hult, "Cavity Enhanced Spectroscopy of High-Temperature H2O in the Near-Infrared Using a Supercontinuum Light Source", Appl. Spectrosc. 63, 12, 1389 (2009). CrossRef C. Abd Alrahman, A. Khodabakhsh, F. M. Schmidt, Z. Qu and A. Foltynowicz, "Cavity-enhanced optical frequency comb spectroscopy of high-temperature H2O in a flame", Opt. Express 22, 11, 13889 (2014). CrossRef A. Foltynowicz, P. Masłowski, A. J. Fleisher, B. J. Bjork and J. Ye, "Cavity-enhanced optical frequency comb spectroscopy in the mid-infrared application to trace detection of hydrogen peroxide", Appl. Phys. B 110, 2, 163 (2013). CrossRef Z. Qu, R. Ghorbani, D. Valiev and F. M. Schmidt, "Calibration-free scanned wavelength modulation spectroscopy ? application to H2O and temperature sensing in flames", Opt. Express 23, 12, 16492 (2015). CrossRef L. Rutkowski, A. Khodabakhsh, A. C. Johansson, D. M. Valiev, et al., "Measurement of H2O and OH in a Flame by Optical Frequency Comb Spectroscopy", CLEO: Science and Innovations SW4H.8 (2016). CrossRef L. S. Rothman, I. E. Gordon, Y. Babikov, A. Barbe, et al., "The HITRAN2012 molecular spectroscopic database", J. Quant. Spectrosc. Radiat. Transf. 130, 4 (2013). CrossRef